High Rate Water Clarification Technology. (Global Journals of Research in Engineering, 2024)
At present the formation of flocculent suspension and its gravity separation are lengthy processes varying between 3 and 4 5 hours Consequently this results in high capital costs Therefore reconsideration of the kinetics of formation of the flocculent suspension and its effect on the gravity separation of formed suspension was needed This reconsideration revealed that an unconventional open-minded thinking was required to develop a new water purification technology capable of solving this problem This technology will most likely be in direct disagreement with the traditional way of thinking in water purification engineering The reconsideration project also revealed that the current method for the use of water soluble polymers results in a deterioration of the purified water quality and detrimentally affects the operation of filters Therefore the development of a method for using these polymers free of side effects is also essential
Keywords: inline high-density suspension formation process; degree of aggregation; organic agglomeration agent; post-orthokinetic